Life tables and population parameters of Helopeltis antonii (Hemiptera: Miridae) reared on cashew (Anacardium occidentale L.) - Siswanto; Muhamad Awang, Rita; Omar, Dzolkhifli; Elna Karmawati (Penerbit Universiti Sains Malaysia, 2008)
Survivorship and fertility of Helopeltis antonii were measured under laboratory and field condition in Wonogiri, Indonesia. Life tables and population parameters for the mirid were constructed based on unlimited food condition and a natural enemies-free environment. The highest mortality occurred in the immature stage, especially on first and second instar of nymphal stages. The survival from egg to adult emergence were about 0.92. The proportion of female to male observed was 1:0.92. The females could live for a maximum of 24 days. Oviposition trend with peak at the end of the female life span. The mean number of eggs produced per female was 6.8. The intrinsic rate of increase (rm) was 0.092 per female per day and daily finite rate of increase (λ) was 1.097 females per female per day, with mean generation time (T) was 27.70 days. The net reproductive rate (Ro) of the population was 12.84. The population double time (DT) was within 7.52 days.